Hubungan Tingkat Pengetahuan Tentang Anemia Dengan Kepatuhan Ibu Hamil Meminum Tablet Zat Besi Di Puskesmas Sengkol - Riezqy Ariendha, Dian Soekmawaty; Pratiwi, Yopi Suryatim; Hardaniyati, Hardaniyati (Jurnal Kesehatan Qamarul Huda, 2019)
The purpose of this study was to research pregnant woman research on anemia with pregnant women using substance tablets at the Sengkol Health Center, Central Lombok District. This research method is an observational study using a cross sectional study, using a questionnaire conducted in March-April 2019 as pregnant women with anemia, samples taken with simple random sampling from 30 respondents, data analysis using univariate analysis, bivariate analysis using chi square. The results of this study were obtained by respondents who had the highest knowledge from mothers who knew about anemia, 27 respondents (90%), and those who did not know about anemia were 3 respondents (10%). Respondents who used tablets using substances were 23 respondents (76.7%), and those who used iron were 7 respondents (23.3%). the results of the analysis using chi-square obtained a relationship associated with the level of knowledge of pregnant women in consuming p-value tablets <? (0.05). Where the value of p = 0.009 because the value of p < ? (0.05). The conclusion is the relationship between the level of knowledge of pregnant women about anemia with the contribution of pregnant substance tablets at the Sengkol Health Center.